Bivariate Distributions and Copula-Tvar Estimates: A Comparative Study Based on The Selected Financial Returns and Marginal Distributions - Iwuji, Anayo Charles; Oruh, Ben Ifeanyichukwu; Nwabueze, Joy Chioma; Okereke, Emmanuel Wilfred (InPrime: Indonesian Journal of Pure and Applied Mathematics, 2024)
This study explores the joint distribution of bivariate financial returns on DJIA-S&P500 and SSE-SZSE, employing copulas and model selection criteria to identify the most suitable distribution. The aim is to estimate Conditional Tail Value at Risk (C-TVaR) at various confidence levels for portfolio risk management. Unlike previous studies, which typically focus on univariate analysis, this research examines into the joint distribution of bivariate financial returns. Additionally, it introduces the application of copulas and model selection criteria to determine the optimal joint distribution for portfolio risk assessment, offering valuable insights for financial decision-makers. Several copulas and model selection criteria are employed to assess the joint distribution of bivariate financial returns. By evaluating the minimum values of model selection criteria such as Akaike Information Criterion (AIC) and Bayesian Information Criterion (BIC), the Student’s t copula is identified as the most appropriate copula. C-TVaR estimates are then obtained at different confidence levels using the selected copula and various combinations of marginal distributions, namely, normal, Student's t, Cauchy, and alpha power transformed logistic (APTL) marginal distributions. Empirical results demonstrate that Student's t copula models with APTL-Student's t and APTL-APTL marginals gave the smallest expected portfolio losses for the DJIA-S&P500 and SSE-SZSE portfolios, respectively. These insights contribute to enhancing portfolio risk management strategies, particularly in assessing tail risk at different confidence levels.Keywords: Alpha power transformed logistic distribution, Bivariate copula, C-TVaR, Model selection criteria, Portfolio loses. AbstrakStudi ini mengeksplorasi distribusi bersama dari keuntungan finansial pada DJIA-S&P500 dan SSE-SZSE, dengan menggunakan kopula dan kriteria pemilihan model untuk mengidentifikasi distribusi yang paling cocok. Tujuannya adalah untuk memperkirakan Conditional Tail Value at Risk (C-TVaR) pada berbagai tingkat kepercayaan untuk manajemen risiko portofolio. Berbeda dengan penelitian sebelumnya, yang umumnya berfokus pada analisis univariat, penelitian ini menyelidiki distribusi bersama dari keuntungan finansial. Selain itu, penelitian ini memperkenalkan aplikasi kopula dan kriteria pemilihan model untuk menentukan distribusi bersama optimal untuk penilaian risiko portofolio, memberikan wawasan berharga bagi pengambil keputusan finansial. Beberapa kopula dan kriteria pemilihan model digunakan untuk menilai distribusi bersama dari keuntungan finansial. Dengan mengevaluasi nilai minimum dari kriteria pemilihan model seperti Akaike Information Criterion (AIC) dan Bayesian Information Criterion (BIC), kopula Student’s t diidentifikasi sebagai kopula yang paling cocok. Estimasi C-TVaR kemudian diperoleh pada tingkat kepercayaan yang berbeda menggunakan kopula yang dipilih dan berbagai kombinasi distribusi marginal, yaitu distribusi marginal normal, Student's t, Cauchy, dan alpha power transformed logistic (APTL). Hasil empiris menunjukkan bahwa model kopula Student's t dengan distribusi marginal APTL-Student's t dan APTL-APTL memberikan ekspetasi kerugian portofolio terkecil untuk masing-masing portofolio DJIA-S&P500 dan SSE-SZSETemuan ini berkontribusi untuk meningkatkan strategi manajemen risiko portofolio, khususnya dalam menilai risiko ekor pada tingkat kepercayaan yang berbeda.Kata Kunci: distribusi Alpha power transformed logistic, Kopula bivariat, C-TVaR, Kriteria pemilihan model, Kehilangan portofolio. 2020MSC: 62H05